2002
DOI: 10.1007/s00401-002-0524-x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix and the blood-brain barrier in glioblastoma multiforme: spatial segregation of tenascin and agrin

Abstract: The quality of the blood-brain barrier (BBB), represented mainly by endothelial tight junctions (TJ), is now believed to be dependent on the brain microenvironment and influenced by the basal lamina of the microvessels. In the highly vascularized glioblastoma multiforme (GBM), a dramatic increase in the permeability of blood vessels is observed but the nature of basal lamina involvement remains to be determined. Agrin, a heparan sulfate proteoglycan, is a component of the basal lamina of BBB microvessels, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(106 citation statements)
references
References 34 publications
7
97
0
2
Order By: Relevance
“…It is well known that basement membrane has a key role in BBB development and stabilization 7,60,67,68 and that laminin and agrin deficiency is associated with BBB alterations. 58,69,70 It is to be noted that both laminin and agrin bind a-b-DG complex, 30 and that, in Muller cells, laminin, by inducing a polarized Kir 4-1 expression, is involved in cleaning excess potassium. 57 Furthermore, it has been demonstrated that, in brain angiogenesis, occurring in both physiological and pathological conditions, basement membrane was degraded by the activity of MMP-2 and MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that basement membrane has a key role in BBB development and stabilization 7,60,67,68 and that laminin and agrin deficiency is associated with BBB alterations. 58,69,70 It is to be noted that both laminin and agrin bind a-b-DG complex, 30 and that, in Muller cells, laminin, by inducing a polarized Kir 4-1 expression, is involved in cleaning excess potassium. 57 Furthermore, it has been demonstrated that, in brain angiogenesis, occurring in both physiological and pathological conditions, basement membrane was degraded by the activity of MMP-2 and MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma is a highly vascularized tumor, and anti-angiogenic therapy has proven effective in reduction of vasogenic edema observed in these patients. In the highly vascularized glioblastoma, a dramatic increase in the permeability of BBB blood vessels was observed, and BBB breakdown was reported by the changes of the molecular compositions of both the endothelial tight junctions and the basal lamina structure (100). Similarly, BBB impairment has been identified as a stable characteristic in patients with mild to moderate Alzheimer's disease.…”
Section: Biodistribution Of Marketed Antibodiesmentioning
confidence: 99%
“…Microscopically, there is increased fenestration of vessel walls, pericyte detachment, and alteration of the extracellular matrix. 59 All events that initate this increased permeability have not been completely defined, but VEGF expression by neoplastic cells is a known cause of increased vascular leakage. 60,61 The end result is that plasma coagulation factors enter tissue spaces where they are activated, leading to the formation of a fibrin plug and platelet aggregation.…”
Section: Intravascular Thrombosis and Vaso-occlusionmentioning
confidence: 99%